Comparative analysis of HPV DNA and LBC for screening of cervical cancer in women with unhealthy cervix - Shreya Raj; Mala Srivastava (Barpeta Obstetrics and Gynaecological Society, 2022)
Background: The cervical cancer is one of the leading cause of cancer death among women in developing and developed countries. Screening for cervical cancer is essential as the women are often asymptomatic and it also reduces both the incidence and mortality of the cancer cervix if detected in early stage. Objectives: We aimed to determine sensitivity and specificity of liquid based cytology (LBC) and HPV DNA to detect pre-neoplastic and neoplastic lesions of cervix. Methods: This was a prospective observational study including 506 women of reproductive, perimenopausal and postmenopausal age group who presented with abnormal vaginal discharge, post coital bleeding, abnormal uterine bleeding, postmenopausal bleeding or had unhealthy cervix on examination, who were subjected to screening by doing LBC and HPV DNA testing. The diagnosis of LBC and HPV DNA was compared against the gold standard of cervical biopsy. The data was entered in MS Excel and analysed using SPSS ver 21.0. A p<0.05 was considered as significant. Results: The mean age of patients in the study was 43.36 years. The sensitivity and specificity of LBC was 76.47%, 43.85%, and that of HPV DNA was 88.23%, 57.89%. The co-testing of LBC and HPV-DNA had a sensitivity and specificity of 94.11% and 24.56%. Discriminatory power of LBC (AUC 0.6; 95% CI: 0.48 to 0.71) and HPV DNA (AUC 0.73; 95% CI: 0.61 to 0.83) was acceptable. Among all the parameters, HPV DNA was the best predictor of pre-invasive or invasive lesion with 73.00% chances of correctly predicting pre-invasive or invasive lesion. Conclusion: Though the early detection and treatment of pre-invasive and invasive lesion of cervix is required, it is important that the best and most sensitive diagnostic tools are used for the screening purposes. Overall HPV DNA was best predictor of pre-invasive or invasive lesion with significantly higher diagnostic accuracy as compared to co-testing.